2022
DOI: 10.3389/fphys.2022.963449
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms-related disorders in diurnal fat sand rats under modern lifestyle conditions: A review

Abstract: Modern lifestyle reduces environmental rhythmicity and may lead to circadian desynchrony. We are exposed to poor day-time lighting indoors and excessive night-time artificial light. We use air-conditioning to reduce ambient temperature cycle, and food is regularly available at all times. These disruptions of daily rhythms may lead to type 2 diabetes mellitus (T2DM), obesity, cardiometabolic diseases (CMD), depression and anxiety, all of which impose major public health and economic burden on societies. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 200 publications
1
0
0
Order By: Relevance
“…These data showed that RF reprogrammed the peripheral lung clock. Our observation correlated with other references that the time of food consumption was a powerful factor affecting the circadian rhythm in metabolically active organs and tissues (Bilu et al, 2022 ; Glad et al, 2011 ; Kim et al, 2023 ; Pickel & Sung, 2020 ; Woodie et al, 2022 ). For lung circadian molecular clock gene expression, such influence was described for tobacco smoking (Choukrallah et al, 2020 ; Khan et al, 2019 ; Numaguchi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…These data showed that RF reprogrammed the peripheral lung clock. Our observation correlated with other references that the time of food consumption was a powerful factor affecting the circadian rhythm in metabolically active organs and tissues (Bilu et al, 2022 ; Glad et al, 2011 ; Kim et al, 2023 ; Pickel & Sung, 2020 ; Woodie et al, 2022 ). For lung circadian molecular clock gene expression, such influence was described for tobacco smoking (Choukrallah et al, 2020 ; Khan et al, 2019 ; Numaguchi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%